(untitled) (Journal of Educational Sciences, 2023)
The issue of teaching world-wide recognized Mukhtar Auezov’s creative activity to school children is presented in this article. Studying the legacy of Mukhtar Auezov in a new way, instilling it into the minds of future generations is an important problem today. It tells about the teaching and reporting of the great work "The path of Abai". In this regard, the school demonstrates the research works of local and foreign scientists on teaching M. Auezov’s works. It is noted that the methodologist and the teacher Bitibaeva Kanipa Omargalievna has an extensive experience in the field of research Abai and Auezov’s creativity. New approaches to the assimilation of the epic novel "The path of Abai" are comprehensively considered in the research works of Kanipa Bitibaeva at school. Scientists are studying the methodology of teaching K. Bitibaeva’s epic novel "The path of Abai" as a whole at school. The teacher proves teaching using the technology of problem analysis of the epic novel "The path of Abai", that is, analysis of the image. The teacher presents simple questions in practice, comparing them with the task of problematic questions. By providing scientific works and additional materials, the author connects the acquired knowledge with life. The reasoned opinion shows that Kanipa Bitibaeva adheres to the position of a person to reveal his thoughts, his inner capabilities. The author analyzes the importance of technology of K. Bitibaeva, suggests applying it in to practice, emphasizes the scientific works and comprehensively studies of search. The teacher concludes that this innovative technology is used by teachers from different parts of the country. The second part of the article reflects the results of experimental work, which was attended by 93 schoolchildren of grades 10-11 of the regional specialized boarding school-gymnasium named after Zhambyl in Ust-Kamenogorsk, East Kazakhstan region and secondary school No. 9 in Altai Key words: teaching an epic novel, problem-based learning, literary text, analysis, national value.